Bixin, an apocarotenoid isolated from Bixa orellana L., sensitizes human melanoma cells to dacarbazine-induced apoptosis through ROS-mediated cytotoxicity. (March 2019) - de Oliveira Júnior, Raimundo Gonçalves; Bonnet, Antoine; Braconnier, Estelle; Groult, Hugo; Prunier, Grégoire; Beaugeard, Laureen; Grougnet, Raphäel; da Silva Almeida, Jackson Roberto Guedes; Ferraz, Christiane Adrielly Alves; Picot, Laurent
Abstract: Cutaneous melanoma has a high capacity to metastasize and significant resistance to conventional therapeutic protocols, which makes its treatment difficult. The combination of conventional drugs with cytostatic molecules of low toxicity has been shown to be an interesting alternative for sensitization of tumor cells to chemotherapy. In this study, we evaluated the effect of bixin, an abundant apocarotenoid present in Bixa orellana, on the sensitization of human melanoma cells (A2058) to dacarbazine treatment, an anticancer agent clinically used for the therapy of metastatic melanoma. UPLC-DAD-MS/MS analyses of bioactive extracts from B. orellana seeds led to the identification of two new apocarotenoids: 6, 8′-diapocarotene-6, 8′-dioic acid and 6, 7′-diapocarotene-6, 7′-dioic acid. After being identified as its major compound, bixin ( Z -bixin) was evaluated on A2058 cells expressing the oncogenic BRAF VE600 mutation and resistant to dacarbazine treatment. Bixin promoted growth inhibition, reduced cell migration, induced apoptosis and cell cycle arrest in the G2/M phase. When associated with dacarbazine, bixin restored the sensitivity of A2058 cells to chemotherapy, enhancing its antiproliferative, anti-migratory and pro-apoptotic effects. Combined treatment also induced higher ROS (reactive oxygen species) and MDA (malondialdehyde, a lipid peroxidation marker) generation than monotreatment, suggesting that the oxidative stress caused by bixin contributes significantly to its sensitizing effect. Taken together, these data suggest that bixin exerts intrinsic antimelanoma activity by mechanisms complementary to those of dacarbazine, encouraging its use in combined therapy for cutaneous melanoma treatment. Graphical abstract: Image 1 Highlights: Identification of two new apocarotenoids (6, 8′-diapocarotene-6, 8′-dioic acid and 6, 7′-diapocarotene-6, 7′-dioic acid). First detection of naringenin and β-12′-apo-carotenoic acid in B . orellana . Purification, characterization and pharmacological evaluation of bixin ( Z- bixin) on human melanoma cells. Sensitization of melanoma cells to dacarbazine treatment by bixin (combined therapy). Potentialization of pro-apoptotic effect of dacarbazine by increasing oxidative stress.